Central Bank Digital Currencies: considerations for a not-too-distant future - Vilela Sampaio, Adriano; Centeno, Vinicius (Brazilian Keynesian Review, 2022)
The central bank digital currencies (CBDC) are subjects of the rising interest of central banks from advanced and emerging economies. Given the relevance and topicality of the subject, this paper seeks to organize the debate that encompasses what is understood as CBDC in the recent international literature, as well as to analyze the possible implications of its implementation. Given that CBDC may assume various forms, there’s still high uncertainty regarding its potential costs and benefits. The decisions concerning the features of the CBDC may have deep implications on various aspects such as the resilience of the domestic financial system, monetary policy effectiveness, functioning of the credit system, and means of payments, among others. Despite the uncertainty associated with the range of possible CBDC architectures, we argue that the strategies of the central banks regarding CBDC may be seen as defensive, as a way to keep up with the technological and cultural changes whilst managing to conduct the process and sustain its central role on the financial system.